Daniels V Anderson : its applications of contributory negligence on auditors’ duty of care in Malaysia / Zeittey Karmilla Kaman and Tan Swee Lim - Kaman, Zeittey Karmilla; Tan, Swee Lim (2010)
As Malaysia gears towards a developed nation by year 2020, we have to prepare ourselves to face and overcome various challenges and complexities, and especially for the businesses to survive. We need to identify a required standard of accountability and liability of auditors, hoping to see a higher degree of social responsibility from auditors. There has been considerable development of the common law principles regarding auditors’ liabilities in recent years. The apportionment of damages for contributory negligence which may be caused by concurrent but independent acts or omissions of two or more parties resulting in a loss suffered by the company will fairly and justly hold every party responsible and liable according to the damage caused by them. Due to these, we need to identify and legislate, if needed, new provisions and use new approaches relevant to this present era to cater for current environment. One of the consideration is to adopt the concept of contributory negligence and the subsequent application of apportionment of liabilities among the company, management and auditors upon any losses resulted from negligence cause by these parties.